EXPERIMENTAL ABILITY EVALUATION OF PASSIVE NAP-OF-THE-EARTH AIRCRAFT TARGET LOCATION USING SEISMIC FIELDS - S. R. Heister (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The acoustic field created by aircraft engine causes generation of seismic field in the ground surface layer. The seismic field may be successfully used to locate nap-of-the-earth (with less than 200 m flight altitude) aircraft. Description of method for passive target location is presented. The range of target detection in accordance with the experimental research of nap-of-the-earth aircraft (airplanes, helicopters) is predicted.